Treatment of purulent complications of soft tissues’ gunshot wounds - Khomenkо I. P.; Tertyshny, S. V.; Gerasimenko, O. S.; Yenin, R. V. (Journal of Education, Health and Sport, 2017)
According to the military operations in the east ofUkraine, the treatment of gunshot wounds became an extremely important problem. The wounded persons need comprehensive treatment using modern approaches one of which is vacuum wound therapy combined with other factors influencing the gunshot wound. A comparative analysis of the complex treatment efficacy of 80 wounded with trunk both soft and an extremities injury was carried out. Complex surgical treatment of wounded with soft tissue’s gunshot wounds purulent complications accelerates the wounds recovery by 1.8 times which allows to shorten significantly the terms of treatment and rehabilitation of the wounded and is an important criterion for determining the effectiveness of the developed technique of complex treatment of soft-tissue gunshot wounds. The use of pulsed negative pressure in the 12 kPa mode in the purulent soft tissue’s wounds complex treatment affected the rate of microflora elimination in the focus of infection and ensured the reduction of the total number of bacteria in the wounds on the 11th day of treatment. Under these conditions, normalization of the main parameters of the peripheral blood, pathobiochemical correlates of the inflammatory process is noted, and also the terms of treatment of blind, through and superficial (tangential) wounds for wounded servicemen are significantly reduced. The proposed treatment program can reduce the severity of the pain syndrome and prevent the further development of gunshot wounds complications.